Storage behaviour and quality responses of mango (Mangifera indica L.) fruit treated with chitosan and gum arabic coatings during cold storage conditions - Khaliq, Ghulam; Tengku Muda Mohamed, Mahmud; Ding, Phebe; Mohd Ghazali, Hasanah; Ali, Asgar (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Natural products are useful for delaying the ripening process, preserving quality and reducing biochemical changes in fruits. Effect of gum arabic (GA) 10% and chitosan (CH) 1% edible coatings on physiological and biochemical properties of mango (Mangifera indica L. cv. Choke Anan) fruit were investigated. Mango fruit were stored at 13°C and 80% relative humidity for 28 days. Significant (P≤0.05) differences were observed in fruits treated with GA 10% and CH 1% as compared to the control. The results showed that GA 10% and CH 1% treatments significantly reduced weight loss than the control fruits. The application of CH 1% coating effectively inhibited the increase in soluble solid concentration (SSC), respiration rate and ethylene production. But no significant differences were observed in terms of ascorbic acid loss between treated fruits and control during the entire storage period. Furthermore, the combined application of GA 10% + CH 1% alleviated decay incidence and retained high firmness of mango fruit. These results suggested that application of GA 10% coating combined with CH 1% as a bio preservative might be a simple and effective technique for delaying ripening and maintaining quality of mango fruit during cold storage without the use of fungicides.